The recognition and management of sepsis and septic shock: a guide for non-intensivists. Issue 1104 (29th July 2017) - Keeley, Alexander; Hine, Paul; Nsutebu, Emmanuel
ABSTRACT: Sepsis is common, often fatal and requires rapid interventions to improve outcomes. While the optimal management of sepsis in the intensive care setting is the focus of extensive research interest, the mainstay of the recognition and initial management of sepsis will occur outside the intensive care setting. Therefore, it is key that institutions and clinicians remain well informed of the current updates in sepsis management and continue to use them to deliver appropriate and timely interventions to enhance patient survival. This review discusses the latest updates in sepsis care including the new consensus definition of sepsis, the outcome of the proCESS, ProMISe and ARISE trials of early goal directed therapy (EGDT), and the most recent guidelines from the Surviving Sepsis Campaign.